N-Methyl-N'-nitro-N-nitrosoguanidine-induced senescence-like growth arrest in colon cancer cells is associated with loss of adenomatous polyposis coli protein, microtubule organization, and telomeric DNA - Jaiswal, Aruna S (BioMed Central, 2004)
BACKGROUND: Cellular senescence is a state in which mammalian cells enter into an irreversible growth arrest and altered biological functions. The senescence response in mammalian cells can be elicited by DNA-damaging agents. In the present study we report that the DNA-damaging agent N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) is able to induce senescence in the HCT-116 colon cancer cell line. RESULTS: Cells treated with lower concentrations of MNNG (0–25 microM) for 50 h showed a dose-dependent increase in G(2)/M phase arrest and apoptosis; however, cells treated with higher concentrations of MNNG (50–100 microM) showed a senescence-like G(0)/G(1 )phase arrest which was confirmed by increased expression of β-galactosidase, a senescence induced marker. The G(2/)M phase arrest and apoptosis were found to be associated with increased levels of p53 protein, but the senescence-like G(0)/G(1 )phase arrest was dissociated with p53 protein levels, since the p53 protein levels decreased in senescence-like arrested cells. We further, determined whether the decreased level of p53 was a transcriptional or a translational phenomenon. The results revealed that the decreased level of p53 protein in senescence-like arrested cells was a transcriptional phenomenon since p53 mRNA levels simultaneously decreased after treatment with higher concentrations of MNNG. We also examined the effect of MNNG treatment on other cell cycle-related proteins such as p21, p27, cyclin B1, Cdc2, c-Myc and max. The expression levels of these proteins were increased in cells treated with lower concentrations of MNNG, which supported the G(2)/M phase arrest. However, cells treated with higher concentrations of MNNG showed decreased levels of these proteins, and hence, may not play a role in cell cycle arrest. We then examined a possible association of the expression of APC protein and telomeric DNA signals with cellular senescence in MNNG-treated cells. We found that protein and mRNA levels of APC were drastically reduced in cells treated with higher concentrations of MNNG. The loss of APC expression might lead to chromosomal instability as well as microtubular disorganization through its dissociation with tubulin. In fact, the protein level of α-tubulin was also drastically decreased in senescence-like arrested cells treated with higher concentrations of MNNG. The levels of telomeric DNA also decreased in cells treated with higher concentrations of MNNG. CONCLUSIONS: These results suggest that in response to DNA alkylation damage the senescence-like arrest of HCT-116 cells was associated with decreased levels of APC protein, microtubular organization, and telomeric DNA.